Hourly sound pressure magnitude data measured underwater on oyster tables during a one-year semi-controlled experiment - Tran, Damien; Botté, Audrey; Geerebaert, Yannick; Payton, Laura (In: Tran, D et al. (2025): Valve behavior of the oysters Crassostrea gigas and Ostrea edulis and physicochemical data measured during a one-year semi-controlled experiment testing the in situ impact of artificial light at night [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.983250, 2025)
This dataset shows the hourly sound pressure magnitude data measured underwater on each oyster table (control and ALAN conditions, at the oyster's level) throughout the year of experiment for different frequencies (10 Hz, 20 Hz, 30 Hz, 40 Hz, 50 Hz, 60 Hz, 70 Hz, 80 Hz, 90 Hz, 100 Hz, 200 Hz, 300Hz, 400 Hz, 500 Hz, 600 Hz, and 700 Hz). The mean sound pressure magnitude is also presented for each condition. In the ALAN condition, data are missing from August 13, 2024, until the end of the experiment due to the failure of the hydrophone used.
Keywords: Arcachon Bay; Artificial Light at Night; Crassostrea gigas; Field experiment; Ostrea edulis; Oyster; physiochemical parameters; valve behavior